Species Composition of Fruit Flies and their Feeding Preferences to Cucurbitaceous Crops in Nepal - Shapkota, Rekha; Thapa, Resham Bahadur; Bajracharya, Ajaya Ratna Shree; K C, Gopal Bahadur; Sharma, Moha D; Dahal, Kishor Chandra (Journal of the Plant Protection Society, 2024)
Fruit fly species (Diptera: Tephritidae: Dacinae: Dacini) have been reported in Nepal, primarily based on field monitoring and specimen collections from cucurbitaceous crops. Their management is effective if the control measures are specific to the damage causing species. Therefore, the total 365 infested flowers/fruits of bitter gourd, cucumber, sponge gourd and zucchini/pumpkin were collected from eastern-western terai and mid-hills of Nepal from 7 July to 27 November in 2022. Each sample was placed in separate plastic jar till the adult emergence. The adult fruit flies were collected from each jar and identified based on morphological features and standard keys under trinocular microscope. At least one fruit fly species emerged as adult fly from 75% samples (n=273). Zeugodacus cucurbitae (Coq.), Z. tau (Walker), Z. scutellaris (Bezzi) and Z. diversus (Coq.) were recorded from 43%, 55%, 25% and 9% of the 273 samples, respectively. Individual flower/fruit sample infested with one, two and three species of fruit flies were 70.3%, 28% and 1.7%, respectively. Z. tau was the most abundant species and accounted for 82.2% while Z. cucurbitae accounted 15.6% of the total emerged adults (7799). Z. cucurbitae and Z. tau emerged from flowers and fruits while Z. scutellaris and Z. diversus largely emerged from flowers. Considering the species composition within genus Zeugodacus, the management strategies should target the damage causing species in field.